100 high burden districts of undernutrition among children and women, in India, in 2019-21 - Gune, Soyra; Christopher, Anita; Singh, Sudhir K.; Sarwal, Rakesh; Bhatia, Neena; Menon, Purnima; Nguyen, Phuong Hong (International Food Policy Research Institute, 2022)
Malnutrition, in all its forms, includes undernutrition (wasting, stunting, underweight), micronutrient deficiencies, overweight, obesity, and diet-related non-communicable diseases such as diabetes and high blood pressure (WHO 2021). This Data Note describes trends in key nutritional outcomes for children and women at the national- and state-levels. The findings are based on data from the National Family Health Survey (NFHS)-4 (2015-2016) and -5 (2019-2021). In addition to standard prevalence-based analyses, this Data Note includes headcount-based analyses at the state-and district-levels, using data from NFHS-5. The goals of POSHAN Abhiyaan are to improve nutritional status of children from 0-6 years, adolescent girls, pregnant women, and lactating mothers in a time-bound manner. Given the district-level focus of POSHAN Abhiyaan, the burden of stunting, underweight, wasting, severe wasting, and anemia were ranked to help identify priority districts with the highest burden of undernutrition among children and women. This Data Note can be used by national-, state-, and district-level officials, non-governmental organizations (NGOs), and research institutes to direct resources and strengthen the implementation of programs and policies to improve these outcomes.